2016
DOI: 10.1007/s00595-016-1448-8
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of C-reactive protein to albumin is a prognostic factor for operable non-small-cell lung cancer in elderly patients

Abstract: The preoperative CAR is a useful predictor of overall survival and could be a simple prognostic tool to help identify resectable NSCLC in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…HRs with 95% CIs were directly obtained from the articles or estimated from the K-M curves according to the methods reported by Tierney et al [19] Statistical heterogeneity among the studies was evaluated with Q and I 2 statistics, with the significance level set at P < .05. [20] If there was significant heterogeneity among the studies, a random effects model was used to calculate the pooled HRs and 95% CIs. [21] Sensitivity analyses to rule out overrepresentation of results from a single study in the meta-analysis were performed by excluding each study individually from the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…HRs with 95% CIs were directly obtained from the articles or estimated from the K-M curves according to the methods reported by Tierney et al [19] Statistical heterogeneity among the studies was evaluated with Q and I 2 statistics, with the significance level set at P < .05. [20] If there was significant heterogeneity among the studies, a random effects model was used to calculate the pooled HRs and 95% CIs. [21] Sensitivity analyses to rule out overrepresentation of results from a single study in the meta-analysis were performed by excluding each study individually from the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Appropriate patient selection is also important when undertaking multimodal therapy. Many recent reports have described the use of prognostic factors involving inflammatory markers such as combinations of neutrophils, platelets, and lymphocytes; 1,2) the C-reactive protein level; and the nutritional status as indicated by the serum albumin and cholesterol levels 15) in both lung cancer 16,17) and MPM although the cutoff values have not been fully investigated. The EORTC prognostic score 13) has also been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer progression simultaneously induces the release of proinflammatory cytokines and promotes the immunovascular system, and neutrophils, lymphocytes, platelets, albumin, and C-reactive protein are affected. 16,17) The detailed mechanism and clinical significance of the inflammatory response have been fully described elsewhere. 15,18) In the present study, only the PLR and EORTC prognostic score were identified as prognostic factors in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The CONUT score was defined based on the total scores for these points. PNI was calculated as 10×the serum albumin level (g/dl)+0.005 × the absolute lymphocyte count (14).CAR was calculated as the ratio of serum CRP (mg/dl) to serum albumin (g/dl) (15). NLR was calculated as the absolute neutrophil count divided by the absolute lymphocyte count (4).…”
Section: Methodsmentioning
confidence: 99%